Textual and language features of students’ written discussion texts - Ting, Su Hie; Chai, A.S (Universiti Malaysia Sarawak (UNIMAS), 2013)
The study examined whether it was more difficult for students to use the macro-organisational structure or the language features of discussion after genre-based instruction. Data were collected from 100 students enrolled in an English for Academic Purposes EAP! course at a "alaysian uni#ersity. They wrote an ad#antages-disad#antages essay which was analysed using $ee%&s 1''(! framewor). The results showed that about half of the students were unable to state the issue clearly at the beginning and assess the issue to conclude the discussion. $or the arguments* the topic sentences and supporting details were satisfactory. The arguments were signposted with se+uential* additi#e and ad#ersati#e connectors* and causal connectors were important for de#eloping the arguments. "odality was con#eyed mainly through ,can and ,we but the potential of conditional clauses to mo#e arguments forward was not realised. The findings indicate that structure deser#es more attention than language features in EAP courses.